2023
DOI: 10.1177/19375867221148168
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Design in the Hospital Environment: A Staff’s Burnout Study in the COVID-19 Era

Abstract: Objective: This study aimed to evaluate the evidence-based design of the hospital physical space effect on the burnout of nurses and physicians during COVID-19. The research question was to identify the connection between daylight, nature-view windows, and hospital staff burnout during Covid-19. Background: The evidence-based design in the hospital environment affects the health of the medical staff. The promotion of the hospital environment has a significant effect on healthcare system improvement. Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This is an essential factor to consider, especially in designing EDs where patients are not supposed to stay for more than a day. Instead, what is gained is boosted energy and stress relief (Golvani et al, 2021), improved sleep quality leading to increased alertness and productivity (Hittle & Wong, 2022; Zadeh et al, 2014), and burnout reduction among staff (Ziabari et al, 2023), leading to quality care for patients. Simulated daylight and natural views might be used for similar positive impacts where the actual interventions, such as windows, skylights, or outdoor patios, are impossible to be implemented (Engwall et al, 2015; Pati et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This is an essential factor to consider, especially in designing EDs where patients are not supposed to stay for more than a day. Instead, what is gained is boosted energy and stress relief (Golvani et al, 2021), improved sleep quality leading to increased alertness and productivity (Hittle & Wong, 2022; Zadeh et al, 2014), and burnout reduction among staff (Ziabari et al, 2023), leading to quality care for patients. Simulated daylight and natural views might be used for similar positive impacts where the actual interventions, such as windows, skylights, or outdoor patios, are impossible to be implemented (Engwall et al, 2015; Pati et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the quality of the neighborhood which provides a good reputation, sense of belonging, and identity will help in citizens' encouragement and empowerment to want to be more social and increase happiness (S03, S04, S07, S09, S12, S13). Societies are affected by the sense of belonging both to their environment and social connections which could be considered by different stakeholders in city development [30][31][32]. Providing an environment that could strengthen the sense of belonging and the identity of people will lead to encouraging social activity and social inclusivity.…”
Section: Social Inclusion and Happinessmentioning
confidence: 99%
“…More recently, a study on caregivers during COVID-19 found that greater amounts of daylight could reduce burnout (Ziabari et al, 2023). An opinion paper by Iqbal and Abubakar (2022) makes a strong case for provision of hospital outdoor spaces as respite areas for care providers.…”
Section: Research On Access To Nature For Caregiversmentioning
confidence: 99%